2016
DOI: 10.1515/aiht-2016-67-2780
|View full text |Cite
|
Sign up to set email alerts
|

Variations in lead, cadmium, arsenic, and mercury concentrations during honeybee wax processing using casting technology

Abstract: Beeswax foundations are a necessary material in intensive modern beekeeping. Heavy metals can accumulate in these foundations for decades, as it is a common beekeeping practice to recycle wax. Beeswax samples were analysed using GFAAS for As, Cd, Pb, and Hg concentrations during the production of beeswax foundations using casting technology with a prolonged cooling and sedimentation phase. Significant differences were determined in the concentrations of As, Cd, Pb (p<0.01, all), and Hg (p<0.05) between the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Furthermore, the analysis of this type of elements in beeswax is infrequent due to the fact that beeswax is not consumed; however, it is important to control the concentration of these elements because beeswax is used in other areas such as biomedicine or in the cosmetic industry. Bee products are useful tools for collecting information about environmental contamination with toxic metals [23,24,25,26]. More precisely, beeswax combs behave like a sink because of the specific lipid-based chemical composition of beeswax [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the analysis of this type of elements in beeswax is infrequent due to the fact that beeswax is not consumed; however, it is important to control the concentration of these elements because beeswax is used in other areas such as biomedicine or in the cosmetic industry. Bee products are useful tools for collecting information about environmental contamination with toxic metals [23,24,25,26]. More precisely, beeswax combs behave like a sink because of the specific lipid-based chemical composition of beeswax [2].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the results obtained in other studies, concentrations of As found in pre-filtered wax and concentrations of Zn existing in post-filtered wax were similar to those found by other authors [21], whereas the other elements studied were in the same range of magnitude, although their values were different, which could be explained by the different geographical origins. Contamination with heavy metals could affect honeybee brood development, after-emergence vitality, queen productivity or longevity of adult bees [25], so the decrease in Hg is a positive effect considering the toxicity of this element for bees and human beings. The decrease in other minerals such as Mn is also beneficial because its ingestion by bees could alter brain levels of biogenic amine, and the exposure to this metal negatively affects the foraging behavior of honeybees [32].…”
Section: Resultsmentioning
confidence: 99%
“…Так, за даними роботи (Formicki et al, 2013), вміст свинцю у меді, зібраному у різних воєводствах Польщі становив 0,06-0,13 мг/кг. У Центральній Хорватії відповідні показники становили 0,09-0,36 мг/кг (Tlak Gajger et al, 2012), у Франціїдо 0,378 мг/кг (Lambert et al, 2012). У зібраному у шести регіонах Аргентини, Бразилії та Венесуели меді спектроскопічні дослідження зафіксували вміст свинцю у меді на рівні 0,11-0,33 мг/кг (Carrero et al, 2012), у Туреччині -0,05-0,48 мг/кг, у Єгипті -0,09-0,64 мг/кг (Hassan et al, 2010).…”
Section: It Was Carried Out Analysis Of Data On Factual Content Of Adunclassified
“…Therefore, comprehensive disinfection of the wooden parts of the hive is possible by combining different methods of heat application, such as immersion of wooden parts in microcrystalline wax (150 • C, 10 min) or using high concentrations of disinfectants [10,11]. However, high concentrations of disinfectants are not economically and environmentally friendly, so implementing preventive zoo-hygienic measures and regularly replacing at least 25-30% of dark, old honeycombs is a very important way to mechanically remove P. larvae spores and other pathogens [12][13][14][15][16][17]. Sporicidal effects on P. larvae were determined for glutaraldehyde and sodium hypochlorite, 0.5% aqueous sodium hypochlorite solution, 1.1% caustic soda solution, and gamma radiation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%